Website to contribute to the development of the rotulian ability in the subject Labor Education (Original) (REDEL. Revista Granmense de Desarrollo Local, 2023)
This article deals with the problem related to the insufficiencies in the development of rotulian ability in seventh grade students of the Bartolomé Masó Márquez Basic Secondary School. Its objective is to evaluate the contribution of the Aprendiendo a Rotular website to the teaching-learning process of seventh grade students of the Bartolomé Masó Márquez Basic Secondary School, based on the development of the rotulian ability in the subject Labor Education. To solve the problem, different research methods were used, corresponding to the theoretical level: inductive-deductive and analytical-synthetic, to the empirical level: observation, survey, documentary analysis, pedagogical test and to the statistical-mathematical: descriptive-statistical, which allowed the design of the website and the processing of data necessary for the research. The validation process of the proposal proved the effectiveness of the informatics product to contribute to the development of rotulian ability in seventh grade students.
Keywords: rotulian ability; website; students of Basic Secondary Education; Labor Education